2023
DOI: 10.3390/s23125723
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Electrocardiogram for Mobile Cardiac Pattern Extraction

Abstract: Background: Internet-of-things technologies are reshaping healthcare applications. We take a special interest in long-term, out-of-clinic, electrocardiogram (ECG)-based heart health management and propose a machine learning framework to extract crucial patterns from noisy mobile ECG signals. Methods: A three-stage hybrid machine learning framework is proposed for estimating heart-disease-related ECG QRS duration. First, raw heartbeats are recognized from the mobile ECG using a support vector machine (SVM). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The CSA underlying the criteria of MMSE was employed to build up a description to quantitatively relate the temperature uncertainty of GS to the temperature changes by minimizing their variances before establishing a mapping model. The CSA is a technique widely used in pattern recognition and other fields [23][24][25][26]. Its essential role is to describe the relationship of the two curves in a mathematical model.…”
Section: The Csamentioning
confidence: 99%
“…The CSA underlying the criteria of MMSE was employed to build up a description to quantitatively relate the temperature uncertainty of GS to the temperature changes by minimizing their variances before establishing a mapping model. The CSA is a technique widely used in pattern recognition and other fields [23][24][25][26]. Its essential role is to describe the relationship of the two curves in a mathematical model.…”
Section: The Csamentioning
confidence: 99%
“…A deep convolutional neural network was employed for feature extraction, while a straightforward neural network with backpropagation was used for classification. In [ 13 ], the authors suggested a framework for machine learning to extract vital patterns from mobile ECG signals. A three-stage hybrid machine learning framework is proposed for estimating ECG duration associated with cardiovascular disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As can be seen from Table 5 , our suggested Residual-Dense-CNN approach performs much better than the other state-of-the-art techniques in terms of the values attained for parameters, accuracy, AUC, kappa, and F1 score. We have compared the RD-CNN model with other techniques such as AlexNet-SVM [ 13 ], CNN-filtering [ 16 ], SVM [ 21 ], CNN-LSTM [ 24 ], RNN-LSTM [ 31 ], DeepCNN [ 33 ], and CNN-Pool [ 34 ]. Compared to other approaches, as mentioned in Table 1 , we have selected these studies because they are easy to implement and because these techniques detect multiclass heart disease.…”
Section: Experimental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, traditional machine-learning-based abnormal detection methods have shown promise in monitoring and predicting the health conditions of humans [ 10 , 11 , 12 ]. These methods utilize machine learning algorithms such as k-nearest neighbor and support vector machines to analyze sensor data, physiological signals, or other relevant features collected from workers to identify abnormal patterns or anomalies that may indicate potential health issues or risks.…”
Section: Introductionmentioning
confidence: 99%